Productivity enhancement and process waste elimination through the use of maynard operation sequence technique - Saravanan Tanjong Tuan (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
To sustain in business under the current fierce competition a company needs to explore all avenues of improvement. In this respect, reduction or elimination of idle and/or down time in operations and improvement of the working methods can play a significant role. This research project is undertaken to address the problems and challenges faced by an auto company in meeting the daily production target of a car rear window assembly line. The operations performed in making this end product are attributable to inefficient work methods with non-optimal capacity planning for different workstations. In this respect Maynard Operation Sequence Technique (MOST) is adopted to exploit the advantages of this PTS system in determining the accurate work standard, analyzing job activity, planning capacity and manpower, and designing workplace. This has helped in re-organizing and allocating jobs for work balancing, and assessing the economic benefit through cost estimation of the existing and proposed processes. Initial investigation shows that the whole assembly line has been suffering from the absence of established standard time for activities carried out by operators, the non-value added activities involved and the inefficient methods such as manual screwing, unplanned aisle and walking distance, material wastages and imbalance in the material flow. Subsequently, by application of MOST alternative methods and work standards are developed which are conducive to capacity planning, workplace layout design and manning analysis. Thus through the process flow analysis, material handling and redistribution of activities among the four workstations an improved process is designed and proposed. It has been revealed that with this proposed method an enhanced workflow is achievable. Upon preliminary introduction of the concept, it has been possible to reduce the production cycle time to cater the higher level of demand with shorter takt time maintaining the current level of manpower. As a result, the production rate is possible to be enhanced from the current level of 54 units to 70 units per day with the suggested operational procedure. This increased capacity is deemed to satisfy the daily production target of 66 units per day. Thus this study also recognizes the effectiveness of the MOST technique to enable an analyst to expose wastes and unproductive methods of work in a quicker manner and help rectify problems at the workplace with an eventual improvement in productivity